NONLINEAR SWITCHED CONTROLLER OF AN AUTONOMOUS TRUCK TRAILER ROBOT FOR VIRTUAL LINE FOLLOWER - Adiyesa (13314050), Paula Kristi Septiani (13314087), Fizri
Applications of automated guided vehicle (AGV) systems exist in recent manufacturing, distribution, transshipment, and transportation areas. Typical example use of AGV is the supplementary automation of standard truck trailer at transshipment systems, such as container terminal. The development of autonomous truck trailer may be collaborated with gantry crane for transportation requests of goods with better performance, high efficiency, and desired effectivity. This research is aimed to design an autonomous truck trailer prototype with the capability of navigating in 3 degree-of-freedoms (x, y, yaw) with regulated consistency and high stability. Mathemathical model of robotÃ‚Â’s kinematic motion is presented in the state space form, and the control systems of the robot is developed using nonlinear control methods. The objective of the controller is designed to follow the rules of the line following and posture stabilization control system. Line following controller algorithm makes sure the robot will always moving on the predetermined trajectory and maintain stable movement when passing through a curve or turning trajectory. In this research, the path to be followed is in the form of virtual line that can be manipulated via control system on the robot. Posture stabilization algorithm makes the robot to find and reach the trajectory when it is outside the track. Switching controller can be added to balance the movement stability of both head and trailer segment. The simulation on a square-shaped trajectory carried out to demonstrate the efficiency of the proposed method by switching point value 0.7 and 3 for the head and trailer controller, respectively. The simulation results show that the switched line following control algorithms can be applied to improve movement stability of the head and trailer by 61.31% and 73.22%, respectively.